Digitalisasi UMKM: Edukasi Strategis dalam Penerapan Digital Marketing dan Legalitas Usaha Online - Mei; Syarohbil Syawal Ahmad Gani; Al Viana Amelia Pratiwi; M. Atilla Rama; Binti Azizatunnafi’ah (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Group 43 of the Community Service Program (KKN) from Universitas Pembangunan Nasional “Veteran”Jawa Timur implemented a community service program in RW 04, Kejawan Putih Tambak, Surabaya. Theinitiative was designed to address the challenges faced by MSMEs in accessing digital tools andunderstanding the importance of business legality. The program aimed to enhance their capacity in digitalmarketing and formal business registration. It was carried out using a participatory approach involvingoutreach, direct assistance, and hands-on practice. The activities were divided into two main stages: digitalmarketing education and technical support, which included logo and banner creation, business locationregistration via Google Maps, and NIB registration through the OSS system. A total of 25 MSMEs took partin the program, with 8 successfully registering for NIB, 6 receiving banners, and 4 obtaining business logos.The results demonstrate the program’s effectiveness in supporting MSMEs’ digital readiness and highlightthe importance of collaborative engagement between students and the community in sustainableempowerment efforts.